2007
DOI: 10.1121/1.2714921
|View full text |Cite
|
Sign up to set email alerts
|

Noise in the operating rooms of Johns Hopkins Hospital

Abstract: Very little reliable information exists on the sound levels present in an operating room environment. To remedy this situation, sound pressure levels of the operating rooms in Johns Hopkins Hospital were monitored before, during, and after operations. The data were analyzed to determine background sound levels, average equivalent sound levels L(eq), frequency distribution, and peak sound pressure levels L(peak). Each surgery was matched to the period of noise it produced permitting the association of sound lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 14 publications
5
74
3
Order By: Relevance
“…The average sound levels measured in these hospitals during daytime were between 52.6 and 64.6 dB, a range similar to those previously reported by other works ( Bayo et al, 1995;Ann et al, 1996;Kracht et al, 2007;Chen et al, 2009 ). However, all of the sound levels measured in the hospitals in the present study were much higher than those suggested by USEPA (i.e., 45 dB during daytime).…”
Section: Sound Levels In Hospitalssupporting
confidence: 78%
See 1 more Smart Citation
“…The average sound levels measured in these hospitals during daytime were between 52.6 and 64.6 dB, a range similar to those previously reported by other works ( Bayo et al, 1995;Ann et al, 1996;Kracht et al, 2007;Chen et al, 2009 ). However, all of the sound levels measured in the hospitals in the present study were much higher than those suggested by USEPA (i.e., 45 dB during daytime).…”
Section: Sound Levels In Hospitalssupporting
confidence: 78%
“…Some researchers reported noise levels in the range of 100 dB to 110 dB from drills, saws and other equipment in operating room were found and this presents a significant risk for noise-induced hearing loss (Love, 2003;Nott and West, 2003). Kracht et al (2007) analyzed the noise in the operating rooms of Johns Hopkins hospital and found orthopedic surgery has the highest average equivalent sound level of approximately 66 dB (A). They also found neurosurgery, urology, cardiology and gastrointestinal surgery have the average equivalent sound levels ranging from 62 to 65 dB(A).…”
Section: Introductionmentioning
confidence: 99%
“…3. A comparative cumulative frequency of the levels of LAeq at each 15-min interval over the daytime (9)(10)(11)(12)(13)(14)(15)(16)(17) and the nighttime (17)(18)(19)(20)(21)(22)(23)(24) in the 16 surveyed hospital lobbies.…”
Section: Noise Measurementsmentioning
confidence: 99%
“…There however is a raging debate as to, is it a distraction with a potential for consequences for patient harm or does it calm a fidgety and timorous Bscalpel wielding hand?Ĉ urrently, most operations are becoming high tech with a lot of electronic gadgetry and their attendant alarms and clatter of moving parts. Further, most surgeries have a plethora of technicians involved, therefore adding to the rush of human personnels in the OR, all contributing to a clamorous caterwauling, which can exceed 120 decibels-louder than a busy highway [1]. Music thus can be construed as adding to this cacophony.…”
mentioning
confidence: 99%